2013
DOI: 10.1037/a0032317
|View full text |Cite
|
Sign up to set email alerts
|

Attentional mechanisms in judging genuine and fake smiles: Eye-movement patterns.

Abstract: We investigated the visual attention patterns (i.e., where, when, how frequently, and how long viewers look at each face region) for faces with (a) genuine, enjoyment smiles (i.e., a smiling mouth and happy eyes with the Duchenne marker), (b) fake, nonenjoyment smiles (a smiling mouth but nonhappy eyes: neutral, surprised, fearful, sad, disgusted, or angry), or (c) no smile (and nonhappy eyes). Viewers evaluated whether the faces conveyed happiness ("felt happy") or not, while eye movements were monitored. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 52 publications
2
37
0
2
Order By: Relevance
“…Although this was in correspondence with the higher pleasantness of happy faces, the relationship was inconsistent with arousal, as happy faces were equally or less arousing than the others. Finally, Calvo, Gutiérrez-García et al (2013) found that the higher valence of happy faces was associated with initial attentional orienting to, and later engagement with, the mouth region, while arousal was not related to the pattern of eye movements. Also, differences in valence and arousal among the other expressions (anger, fear, sadness, disgust and surprise) were not consistently associated with any overt attention pattern.…”
Section: Do Affective Intensity Differences Explain Recognition Accurmentioning
confidence: 94%
See 1 more Smart Citation
“…Although this was in correspondence with the higher pleasantness of happy faces, the relationship was inconsistent with arousal, as happy faces were equally or less arousing than the others. Finally, Calvo, Gutiérrez-García et al (2013) found that the higher valence of happy faces was associated with initial attentional orienting to, and later engagement with, the mouth region, while arousal was not related to the pattern of eye movements. Also, differences in valence and arousal among the other expressions (anger, fear, sadness, disgust and surprise) were not consistently associated with any overt attention pattern.…”
Section: Do Affective Intensity Differences Explain Recognition Accurmentioning
confidence: 94%
“…Valence ratings are generally consistent: Happy faces are judged as more pleasant than any other expression or neutral faces, which are rated as more pleasant than the negatively valenced basic expressions. This pattern has been obtained with various face databases (POFA: Lipp, Price, &Tellegen, 2009, andBullock, 1985;KDEF: Calvo, Gutiérrez-García, Avero, &Lundqvist, 2013, andEisenbarth, Alpers, Segré, Calogero, &Angrilli, 2008;or both KDEF and NimStim: Adolph & Alpers, 2010). For arousal ratings, the pattern is much less consistent: happy faces are more arousing than neutral or other emotional faces (Eisenbarth et al, 2008), or equally arousing as angry faces (Calvo, Gutiérrez-García et al, 2013;Lipp et al, 2009, Experiment 2), or equally arousing as angry and fearful faces (Adolph & Alpers, 2010), or less arousing than angry and fearful faces (Russell & Bullock, 1985;Lipp et al, 2009, Experiment 3).…”
Section: Affective Processing and Fac-ial Expression Recognitionmentioning
confidence: 99%
“…Así, resulta difícil encontrar experiencias previas en que se explore la lectura de géneros académicos y profesionales y, mucho más exigua, o incluso inexistente, es la literatura que aborde el procesamiento de este tipo de géneros en español en que interactúen diversos sistemas semióticos, tales como palabras y gráficos. Sí se identifica investigación con tecnología ET pero en otros dominios, tales como, estudios únicamente del sistema verbal (Calvo, Meseguer & Carreiras, 2001;Calvo & Meseguer, 2002;Loureda, Nadal & van Vliet, 2011;Betancort, Carreiras & Sturt, 2011;Fernández, Shalom, Kliegl & Sigman, 2014;Loureda, Cruz, Rudka, Nadal & Zuloaga, 2015), de usabilidad en sistemas de interacción entre seres humanos e interfaces computacionales (Loyola, Martínez & Velásquez, 2014;Slanzy, Jadue & Velásquez, 2015), de reconocimiento de emociones y gestos faciales (Calvo, Gutiérrez-García, Avero & Lundqvist, 2013;Fernández-Martín, Gutiérrez-García & Gutiérrez-Calvo, 2013), de mercadotecnia o visualización (González & Velásquez, 2012) o los que se abocan a textos compuestos por palabras e imágenes o ilustraciones (Añaños & Astals, 2013).…”
Section: Introductionunclassified
“…Upitnik se sastojao od 20 stavaka, s obzirom na prisutnost ljuFace and smile esthetics are significant components of the contemporary communication in politics and political marketing where political parties spend a vast amount of money to address their thoughts and messages with the help of media, marketing and public relation experts (8). An attractive smile helps winning the elections (8), also, attractive people are considered to be intelligent, successful, fair and compassionate because of the common belief -what is beautiful is considered good (2,3,6).…”
Section: Materijali I Postupcimentioning
confidence: 99%
“…Privlačan osmijeh pomaže pobijediti na izborima (8), a također se smatra da su privlačni ljudi inteligentni, uspješni, pravedni i suosjećajni zbog općeg vjerovanja da je dobro sve što je lijepo (2,3,6).…”
unclassified